Методика анализа аварийных рисков и прогноза отказов региональных распределительных систем газоснабжения (РРСГ) - Седак, В. С.; Рыбников, Н. Я.; Каслин, Н. Д. (Національний технічний університет "Харківський політехнічний інститут", 2011)
Анализируются объективные и субъективные факторы обеспечения безопасности системы газоснабжения и методы повышения ее надежности. Предложен алгоритм расчета аварийного риска распределительных газопроводов для обеспечения повышения их надежности и снижения отказов. Разработано "дерево" отказов для подземных газопроводов.

Нe objective and subjective factors of complication of providing of safety of the system of gas-supplying are analyzed and methods of increase of fail safety gas-supplying. The algorithm of emergency risk of distributive gas pipelines is offered for providing of increase of reliability and decline of risks of failures. The tree of refusals is developed for underground gas pipelines.
Method of analysis of emergency risks and prognosis of refuses of regional distributive systems of gas-supplying (RRDSG)
Keywords: система газоснабжения; метод повышения надежности; аварийный риск; отказ; газопровод; эксплуатация систем газоснабжения; system of gas-supplying; fail safety; gas pipelines